2021
DOI: 10.1186/s12935-020-01684-z
|View full text |Cite
|
Sign up to set email alerts
|

miR-335-5p suppresses gastric cancer progression by targeting MAPK10

Abstract: Background Recent studies have established the roles of microRNAs (miRNAs) in cancer progression. The aberrant expression of miR-335-5p has been reported in many cancers, including gastric cancer (GC). In this study, the precise roles of miR-335-5p in GC as well as the molecular mechanisms underlying its effects, including the role of its target MAPK10, were evaluated. Methods Quantitative real-time PCR was used to evaluate miR-335-5p levels in GC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…In this, we pointed out that circ‐ZNF644 could sponge miR‐335‐5p. MiR‐335‐5p has been discovered to be a tumor suppressor in many cancer 27,28 . MiR‐335‐5p was considered to be an inflammation‐related miRNA, and its upregulation could effectively inhibit inflammation 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this, we pointed out that circ‐ZNF644 could sponge miR‐335‐5p. MiR‐335‐5p has been discovered to be a tumor suppressor in many cancer 27,28 . MiR‐335‐5p was considered to be an inflammation‐related miRNA, and its upregulation could effectively inhibit inflammation 29 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-335-5p has been discovered to be a tumor suppressor in many cancer. 27,28 MiR-335-5p was considered to be an inflammation-related miRNA, and its upregulation could effectively inhibit inflammation. 29 Studies has shown that miR-335-5p was a regulator to be related to sepsis patient's mortality, which could suppress inflammatory responses, so it might be a candidate treatment target for patients with sepsis.…”
Section: Mir-335-5p Inhibited Lps-induced Hk2 Cell Injury By Hipk1mentioning
confidence: 99%
“…There is increasing evidence that it acts as a microRNA target to play a tumor-promoting or tumorsuppressing role [23][24][25]. Gao et al [26] revealed that miR-335-5p suppressed GC progression by targeting MAPK10. In addition, we found that IFNA4 and IFNB1 were reported in cyclic GMP-AMP synthase-stimulator of interferon (cGAS-STING) related prognostic signatures in GC [27].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to lncRNAs, microRNAs (miRNAs) are about 18–25 bases long, without a protein-coding function. In recent years, emerging evidence has pointed out that miRNAs regulate tumors’ malignant phenotype and then affect tumor progression [ 29 , 30 , 31 ]. In addition [ 32 ], DARS-AS1 can act as a competitive endogenous RNA to sponge miRNAs, thereby choking the effects of targeted miRNAs.…”
Section: Discussionmentioning
confidence: 99%